2024
DOI: 10.14336/ad.2023.0630-1
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Cellular Senescence, and Glaucoma

Yumeng Zhang,
Shouyue Huang,
Bing Xie
et al.

Abstract: Aging is one of the most serious risk factors for glaucoma, and according to age-standardized prevalence, glaucoma is the second leading cause of legal blindness worldwide. Cellular senescence is a hallmark of aging that is defined by a stable exit from the cell cycle in response to cellular damage and stress. The potential mechanisms underlying glaucomatous cellular senescence include oxidative stress, DNA damage, mitochondrial dysfunction, defective autophagy/mitophagy, and epigenetic modifications. These ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…The condition is characterized by the accelerated loss of retinal neurons and their axons, often coexisting with other age-related eye diseases that share molecular mechanisms resulting from repeated light damage and subsequent oxidative stress [132]. Aging contributes to abnormal peripheral blood flow, vascular stenosis, and endothelial dysfunction, all closely linked to the development of glaucoma [133]. Studies have found that in addition to increased intraocular pressure, an important risk factor, increased glutamate levels, changes in nitric oxide (NO) metabolism, vascular changes, and oxidative damage caused by ROS are also important factors in glaucoma [134].…”
Section: Molecular Insights Into Retinal Vascular Aging: the Pivotal ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The condition is characterized by the accelerated loss of retinal neurons and their axons, often coexisting with other age-related eye diseases that share molecular mechanisms resulting from repeated light damage and subsequent oxidative stress [132]. Aging contributes to abnormal peripheral blood flow, vascular stenosis, and endothelial dysfunction, all closely linked to the development of glaucoma [133]. Studies have found that in addition to increased intraocular pressure, an important risk factor, increased glutamate levels, changes in nitric oxide (NO) metabolism, vascular changes, and oxidative damage caused by ROS are also important factors in glaucoma [134].…”
Section: Molecular Insights Into Retinal Vascular Aging: the Pivotal ...mentioning
confidence: 99%
“…Studies have found that in addition to increased intraocular pressure, an important risk factor, increased glutamate levels, changes in nitric oxide (NO) metabolism, vascular changes, and oxidative damage caused by ROS are also important factors in glaucoma [134]. Cellular senescence has been shown to lead to impaired angiogenesis, with multiple studies finding reduced retinal blood flow and capillary density in patients with glaucoma [133]. In patients with glaucoma with impaired retinal vascular function and reduced retinal vascular reactivity, RGCs and their axons are exposed to increased oxidative stress, which leads to further progression of glaucomatous damage [135].…”
Section: Molecular Insights Into Retinal Vascular Aging: the Pivotal ...mentioning
confidence: 99%
See 1 more Smart Citation